Book Reviews. Issue 1 (1st March 2019) - Serna, Laura Isabel; Murray, N. Michelle; Medina, Raquel; Stone, Rob; Ramírez-Soto, Elizabeth; Alvaray, Luisela; Gasiorowski, Dominika; Hansen, Audrey; Hopfenblatt, Alejandro Kelly; Norton, Diana
Jenkins of Mexico: How a Southern Farm Boy became a Mexican Magnate, Andrew Paxman (2017) Oxford: Oxford University Press, 544 pp., ISBN: 978-0-19045-574-3, h/bk, 34.95Confessional Cinema: Religion, Film, and Modernity in Spain's Development Years, 1960–1975, Jorge Pérez (2017) Toronto: University of Toronto Press, 280 pp., ISBN: 978-1-48750-108-2, h/bk, 70.00Affect and Belonging in Contemporary Spanish Fiction and Film. Crossroads Visions, Jesse Barker (2017) Cham: Palgrave Macmillan, 226 pp., ISBN 978-3-31957-964-1, h/bk, £67.99Cinema at the Edges: New Encounters with Julio Medem, Bigas Luna and José Luis Guerín, Abigail Loxham (2014) New York and Oxford: Bergahn, 202 pp. ISBN: 978-1-78238-304-8, h/bk, £64.00; eISBN: 978-1-78238-305-5, eBook, £52.00Raúl Ruiz's Cinema of Inquiry, Ignacio López-Vicuña and Andreea Marinescu (eds) (2017) Detroit: Wayne State University Press, 260 pp., ISBN: 978-0-81434-106-3, p/bk, 36.99Cines del Sur: La integración cinematográfica entre los países del Mercosur, Marina Moguillansky (2016) Buenos Aires: Editorial Imago Mundi, 248 pp., ISBN 978-9-50793-227-4, p/bk, 430 ARSLatin American Women Filmmakers: Production, Politics, Poetics, Deborah Shaw and Deborah Martin (eds) (2017) London and New York: I.B. Tauris, 288 pp., ISBN: 978-1-78453-711-1, h/bk, £62El cine de Agüero: El documental como la lectura de un Espacio, Valeria De Los Ríos And Catalina Donoso (2015) Santiago de Chile: Editorial Cuarto Propio, 167 pp., ISBN 978-9-56260-716-2, p/bk, 8.600 CLPChilefilms, el Hollywood criollo: Aproximaciones al proyecto industrial cinematográfico chileno (1942–1949), María Paz Peirano and Catalina Gobantes (eds) (2015) Santiago: Editorial Cuarto Propio, 286 pp., ISBN 978-9-56260-694-3, p/bk, 11.400 CLPCrónica de un encuentro. El cine mexicano en España, 1933–1948, Ángel Miquel (2016) Mexico City: Dirección General de Actividades Cinematográficas, 284 pp., ISBN 978-6-07027-849-5, 798 MXN, p/bk, 9.99